Direct taxation in the EU: the common corporate tax base as the next sub-step towards harmonization - Herzig, Norbert; Kuhr, Johannes (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
This paper analyzes the Common Corporate Tax Base (CCTB) as an interim alternative to the proposal of a Council directive on a Common Consolidated Corporate Tax Base (CCCTB). The CCCTB concept does not only include common rules for determining the tax base like the CCTB but also the steps of consolidation and subsequent formula apportionment. Therefore, the paper starts by showing that particularly these second and third steps of the CCCTB project meet fierce political opposition from several Member States and do leave leeway for tax planning. Afterwards, the CCCTB proposal's approach to common rules for determining the tax base is evaluated, i.e. tested for its suitability as a point of departure for drafting a CCTB. Finally, various other aspects of the proposal are examined in light of a CCTB without consolidation.
Keywords: Unia Europejska; opodatkowanie osób prawnych; podstawa opodatkowania